Bibliometric Analysis of Research Trends and Opportunities on the Infection of HIV and Tuberculosis: 2013 – 2024 Data Collection - Nurmansyah, Dian; Puspawati, Puspawati; Putri Ayanti, Bio; Valentine Gunasari, Lala Foresta; Lystirini, Eka (Jurnal KESANS : Kesehatan dan Sains, 2025)
Tuberculosis (TB) and HIV co-infection remains a critical problem in public health, particularly in Indonesia, which carries a high disease burden. A preliminary literature review reveals a significant gap in research from Indonesian institutions, highlighting the urgent need for a systematic analysis of the existing scientific landscape. This bibliometric study, conducted using the Scopus database from 2010 to 2023, aims to map publication trends, key contributors, and emerging research themes related to TB-HIV. The analysis shows a consistent increase in publications over the last decade, with research driven by a strong collaborative network led by highly prolific authors and dominated by Brazilian institutions. Visualizations indicate a shift in research focus from specific HIV-related topics to broader aspects of TB, drug resistance, and patient demographics. Despite the diversification of global contributions with a growing presence from countries in Africa and Asia, Indonesia's representation remains limited. This presents a compelling opportunity for Indonesian researchers to increase their involvement and contribute to the global scholarly discourse on this issue, addressing a national and international health challenge.